2012
DOI: 10.2165/11630660-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Estrogen Treatment in the Management of Schizophrenia

Abstract: Increasing evidence from epidemiological, preclinical and clinical studies suggests that estrogens may exert psychoprotective effects in schizophrenia. Observations of gender differences in the onset and course of schizophrenia have prompted exploration of the effects of estrogen on the CNS. The aim of this paper is to provide an overview of different applications of adjunctive estrogen as a possible treatment for symptoms of schizophrenia in both men and women. Recent trials have suggested that estrogen augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 80 publications
1
42
0
Order By: Relevance
“…Furthermore, sex differences have been described for nearly all features of schizophrenia [114]. Clinical studies suggest that estrogens exert psychoprotective effects in schizophrenia patients [115] which may be mediated by an interaction effect between estrogen and brain-derived neurotrophic factor (BDNF) [114]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sex differences have been described for nearly all features of schizophrenia [114]. Clinical studies suggest that estrogens exert psychoprotective effects in schizophrenia patients [115] which may be mediated by an interaction effect between estrogen and brain-derived neurotrophic factor (BDNF) [114]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, men have an earlier age of disease onset, more deficit symptoms and a poorer response to antipsychotic drug treatment (Lindamer et al, 1997). Additionally, sex differences also exist regarding structural and functional brain abnormalities that may underlie the disease pathology (Cascio et al, 2012;Kulkarni et al, 2012;Gonzalez-Rodriguez et al, 2014). However, In the present study, we aimed at further characterizing the effects of prenatal LPS exposure on 5-HT 2A and mGlu2/3 receptor function in the adult rat offspring.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…Previous research on this issue reported conflicting results, with some studies reporting a better outcome in men [23] and other in women [32]. In this case, some Authors suggested a possible protective role for estrogens through a direct anti-dopaminergic effect, although data are still lacking to draw definitive conclusions about this hypothesis [33].…”
Section: Discussionmentioning
confidence: 91%